Emission inventories of rice straw open burning in the Red River Delta of Vietnam: Evaluation of the potential of satellite data. (May 2020) - Le, Hoang Anh; Phuong, Do Minh; Linh, Le Thuy
Abstract: Although rice straw open burning is one of the main sources of air pollution in Asian countries, problems remain in collecting the activity data needed to calculate emission inventories. In Vietnam, the results from traditional data collection methods, which are reported by the Vietnam General Statistics Office high levels of uncertainty. This is largely due to a lack of human and financial resources. To improve upon this, this study critically assessed the benefits of incorporating cultivation area data obtained by the Sentinel-1 Synthetic Aperture Radar (SAR) satellite in combination with crop production records during the period of 2015–2017. The results suggested that incorporating remote sensing data, especially satellite data, into a process-based crop model can improve the spatial distribution of yield estimates. Satellite data for 2018 were also applied to estimate emissions from rice straw open burning in the Red River Delta, Vietnam, for which official statistics are not otherwise yet available. The results show that a total of 3.24 Mt of burnt rice straw produced 3.82 Mt of CO2, 301 Gg of CO, 29.5 Gg of PM10, and 27 Gg of PM2.5 . The estimated emission amounts for the common air pollutants SO2, NOx, and NH3 were 583 tonnes, 7.4 Gg, and 13.3 Gg, respectively. Hydrocarbon emissions were 31 Gg for CH4 and 22.7 Gg for NMVOC. The emission of BC, which is one of the main short-lived climate forcers, totalled 1.6 Gg. Based on these results, satellite data demonstrate great potential for estimating emissions from rice croplands, having the advantages of timely availability and cost competitiveness. Graphical abstract: Image 1 Highlights: Sentinel-1 images integrated with ORYZA 2000 model improve crop-growth data. New crop datasets reduce uncertainties by 10–12.4% compared to traditional methods. 29.5 Gg of PM10, 27 Gg of PM2.5, 1.6 Gg of BC emitted in the Red River Delta (2018). 3.82 Mt of CO2 contributed the most to air emissions from rice straw open burning.